Gain-of-Function Research: Summary of the Second Symposium, March 10-11, 2016 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On March 10-11, 2016, the National Academies of Sciences, Engineering, and Medicine held a public symposium on potential U.S. government policies for the oversight of gain-of- function (GOF) research. This was the Academies' second meeting held at the request of the U.S. government to provide a mechanism to engage the life sciences community and the broader public and solicit feedback on optimal approaches to ensure effective federal oversight of GOF research as part of a broader U.S. government deliberative process. The first symposium, held in December 2014, examined the underlying scientific and technical questions surrounding the potential risks and benefits of GOF research involving pathogens with pandemic potential. The second symposium focused on discussion of the draft recommendations regarding GOF research of a Working Group of the National Science Advisory Board for Biosecurity. This report summarizes the key issues and ideas identified during the second symposium.
Keywords: Health and Medicine

Globalization, Biosecurity, and the Future of the Life Sciences - Institute of Medicine; National Research Council (The National Academies Press, 2006)
Biomedical advances have made it possible to identify and manipulate features of living organisms in useful ways—leading to improvements in public health, agriculture, and other areas. The globalization of scientific and technical expertise also means that many scientists and other individuals around the world are generating breakthroughs in the life sciences and related technologies. The risks posed by bioterrorism and the proliferation of biological weapons capabilities have increased concern about how the rapid advances in genetic engineering and biotechnology could enable the production of biological weapons with unique and unpredictable characteristics. Globalization, Biosecurity, and the Future of Life Sciences examines current trends and future objectives of research in public health, life sciences, and biomedical science that contain applications relevant to developments in biological weapons 5 to 10 years into the future and ways to anticipate, identify, and mitigate these dangers.
Keywords: Biology and Life Sciences; Conflict and Security Issues; Policy for Science and Technology

The 2nd International Forum on Biosecurity: Summary of an International Meeting - National Research Council (The National Academies Press, 2009)
The 2nd International Forum on Biosecurity, held in Budapest, Hungary on March 30 - April 2, 2008, represents the efforts of a number of individuals and organizations, over the last five years, to engage the international community of life scientists in addressing how to reduce the risk that the results of their work could be used for hostile purposes by terrorists and states. The participants who gathered in Budapest were already engaged in this challenging task, and, therefore, the focus of the meeting was on what had been accomplished and what challenges remained. There was no attempt to achieve consensus, since there exist real and important differences among those involved concerning the appropriate policies and actions to be undertaken. But there was a serious effort to identify a range of potential next steps, and also an effort to identify opportunities where international scientific organizations could make substantive contributions and offer their advice and expertise to policy discussions. The Forum's presentations, discussions, and results are summarized in this book.
Keywords: Conflict and Security Issues

Dual Use Research of Concern in the Life Sciences: Current Issues and Controversies - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The potential misuse of advances in life sciences research is raising concerns about national security threats. Dual Use Research of Concern in the Life Sciences: Current Issues and Controversies examines the U.S. strategy for reducing biosecurity risks in life sciences research and considers mechanisms that would allow researchers to manage the dissemination of the results of research while mitigating the potential for harm to national security.
Keywords: Policy for Science and Technology

Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories: Summary of a Workshop - National Academy of Sciences; National Research Council (The National Academies Press, 2012)
During July 10-13, 2011, 68 participants from 32 countries gathered in Istanbul, Turkey for a workshop organized by the United States National Research Council on Anticipating Biosecurity Challenges of the Global Expansion of High-containment Biological Laboratories. The United States Department of State's Biosecurity Engagement Program sponsored the workshop, which was held in partnership with the Turkish Academy of Sciences. The international workshop examined biosafety and biosecurity issues related to the design, construction, maintenance, and operation of high-containment biological laboratories- equivalent to United States Centers for Disease Control and Prevention biological safety level 3 or 4 labs. Although these laboratories are needed to characterize highly dangerous human and animal pathogens, assist in disease surveillance, and produce vaccines, they are complex systems with inherent risks. Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories summarizes the workshop discussion, which included the following topics: Technological options to meet diagnostic, research, and other goals; Laboratory construction and commissioning; Operational maintenance to provide sustainable capabilities, safety, and security; and Measures for encouraging a culture of responsible conduct. Workshop attendees described the history and current challenges they face in their individual laboratories. Speakers recounted steps they were taking to improve safety and security, from running training programs to implementing a variety of personnel reliability measures. Many also spoke about physical security, access controls, and monitoring pathogen inventories. Workshop participants also identified tensions in the field and suggested possible areas for action.
Keywords: Conflict and Security Issues; Biology and Life Sciences

Perspectives on Research with H5N1 Avian Influenza: Scientific Inquiry, Communication, Controversy: Summary of a Workshop - Institute of Medicine; National Research Council (The National Academies Press, 2013)
When, in late 2011, it became public knowledge that two research groups had submitted for publication manuscripts that reported on their work on mammalian transmissibility of a lethal H5N1 avian influenza strain, the information caused an international debate about the appropriateness and communication of the researchers' work, the risks associated with the work, partial or complete censorship of scientific publications, and dual-use research of concern in general. Recognizing that the H5N1 research is only the most recent scientific activity subject to widespread attention due to safety and security concerns, on May 1, 2012, the National Research Council's Committee on Science, Technology and Law, in conjunction with the Board on Life Sciences and the Institute of Medicine's Forum on Microbial Threats, convened a one-day public workshop for the purposes of 1) discussing the H5N1 controversy; 2) considering responses by the National Institute of Allergy and Infectious Diseases (NIAID), which had funded this research, the World Health Organization, the U.S. National Science Advisory Board for Biosecurity (NSABB), scientific publishers, and members of the international research community; and 3) providing a forum wherein the concerns and interests of the broader community of stakeholders, including policy makers, biosafety and biosecurity experts, non-governmental organizations, international organizations, and the general public might be articulated. Perspectives on Research with H5N1 Avian Influenza: Scientific Enquiry, Communication, Controversy summarizes the proceedings of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Countering Biological Threats: Challenges for the Department of Defense's Nonproliferation Program Beyond the Former Soviet Union - National Research Council (The National Academies Press, 2009)
In response to a request from the U.S. Congress, this book examines how the unique experience and extensive capabilities of the Department of Defense (DOD) can be extended to reduce the threat of bioterrorism within developing countries outside the former Soviet Union (FSU). During the past 12 years, DOD has invested $800 million in reducing the risk from bioterrorism with roots in the states of the FSU. The program's accomplishments are many fold. The risk of bioterrorism in other countries is too great for DOD not to be among the leaders in addressing threats beyond the FSU. Taking into account possible sensitivities about a U.S. military presence, DOD should engage interested governments in about ten developing countries outside the FSU in biological threat reduction programs during the next five years. Whenever possible, DOD should partner with other organizations that have well established humanitarian reputations in the countries of interest. For example, the U.S. Agency for International Development, the Centers for Disease Control and Prevention, and the World Health Organization should be considered as potential partners.
Keywords: Conflict and Security Issues

Understanding Biosecurity: Protecting Against the Misuse of Science in Today's World - National Research Council (The National Academies Press, 2010)
Drawing on the work of the National Academies, this booklet introduces some of the issues at the intersection of science and security. The life sciences offer tremendous promise for meeting many 21st century challenges. But with opportunities come responsibilities. An important aspect of scientists' responsibility to society is captured in the concept of biosecurity-- the challenge to move the life sciences forward for legitimate purposes while reducing the risks that some materials, knowledge, tools, and technologies could also be used to do harm. This booklet was developed to serve as an educational resource for students and the scientific community, to illuminate the importance of biosecurity, and to explore how scientists, organizations, and governments at many levels can work together to minimize the threat.
Keywords: Policy for Science and Technology; Conflict and Security Issues

Biotechnology Research in an Age of Terrorism - National Research Council (The National Academies Press, 2004)
In recent years much has happened to justify an examination of biological research in light of national security concerns. The destructive application of biotechnology research includes activities such as spreading common pathogens or transforming them into even more lethal forms. Policymakers and the scientific community at large must put forth a vigorous and immediate response to this challenge. This new book by the National Research Council recommends that the government expand existing regulations and rely on self-governance by scientists rather than adopt intrusive new policies. One key recommendation of the report is that the government should not attempt to regulate scientific publishing but should trust scientists and journals to screen their papers for security risks, a task some journals have already taken up. With biological information and tools widely distributed, regulating only U.S. researchers would have little effect. A new International Forum on Biosecurity should encourage the adoption of similar measures around the world. Seven types of risky studies would require approval by the Institutional Biosafety Committees that already oversee recombinant DNA research at some 400 U.S. institutions. These "experiments of concern" include making an infectious agent more lethal and rendering vaccines powerless.
Keywords: Conflict and Security Issues; Policy for Science and Technology

Challenges and Opportunities for Education About Dual Use Issues in the Life Sciences - National Research Council (The National Academies Press, 2011)
The Challenges and Opportunities for Education About Dual Use Issues in the Life Sciences workshop was held to engage the life sciences community on the particular security issues related to research with dual use potential. More than 60 participants from almost 30 countries took part and included practicing life scientists, bioethics and biosecurity practitioners, and experts in the design of educational programs. The workshop sought to identify a baseline about (1) the extent to which dual use issues are currently being included in postsecondary education (undergraduate and postgraduate) in the life sciences; (2) in what contexts that education is occurring (e.g., in formal coursework, informal settings, as stand-alone subjects or part of more general training, and in what fields); and (3) what online educational materials addressing research in the life sciences with dual use potential already exist.
Keywords: Biology and Life Sciences; Education; Policy for Science and Technology; Conflict and Security Issues

Responsible Research with Biological Select Agents and Toxins - National Research Council (The National Academies Press, 2009)
The effort to understand and combat infectious diseases has, during the centuries, produced many key advances in science and medicine—including the development of vaccines, drugs, and other treatments. A subset of this research is conducted with agents that, like anthrax, not only pose a severe threat to the health of humans, plants, and animals but can also be used for ill-intended purposes. Such agents have been listed by the government as biological select agents and toxins. The 2001 anthrax letter attacks prompted the creation of new regulations aimed at increasing security for research with dangerous pathogens. The outcome of the anthrax letter investigation has raised concern about whether these measures are adequate. Responsible Research with Biological Select Agents and Toxins evaluates both the physical security of select agent laboratories and personnel reliability measures designed to ensure the trustworthiness of those with access to biological select agents and toxins. The book offers a set of guiding principles and recommended changes to minimize security risk and facilitate the productivity of research. The book recommends fostering a culture of trust and responsibility in the laboratory, engaging the community in oversight of the Select Agent Program, and enhancing the operation of the Select Agent Program.
Keywords: Conflict and Security Issues; Biology and Life Sciences